Evaluation of Antimicrobial Activity of Selected Plant Extracts against Staphylococcus Strains Isolated from Wound Infections - Pietruczuk-Padzik, Anna; Śliwińska, Milena; Mainka, Marta; Czerwińska, Monika E.; Skowrońska, Weronika; Bazylko, Agnieszka (Planta Medica, 2024)
Wound infections are a significant medical problem, with Staphylococcus species being one of the most common etiological factors. Treatment is complex due to bacterial antibiotic resistance and the ability to form a biofilm. The aim of this study was to determine the drug susceptibility of the clinical isolates of Staphylococcus species obtained from wound infections, assess their ability to form a biofilm in vitro, evaluate the level of extracellular slime synthesis, and test the antistaphylococcal properties of selected plant extracts against plate-cultured bacteria and activity against mature biofilms. A total of 20 Staphylococcus strains were evaluated. The antibiotic susceptibility and sensitivity of the strains to the tested extracts were determined using the disc diffusion method. The production of extracellular bacterial slime was assessed using Congo Red agar plates. The biofilm formation and the effect of plant extracts on the biofilm layer were examined using the MTT method on polystyrene microtiter plates. Diverse drug susceptibility profiles, slime production ability, and in vitro biofilm formation were observed among the tested strains. It was found that aqueous extracts from the Serpylli herba, Arctii lappae folium, Taraxaci folium, and Galii aparini herba showed antibacterial activity against some of the tested strains. In contrast, their antibiofilm activity was not confirmed. Among all tested preparations, the most promising antimicrobial extracts in both planktonic cultures and biofilm were Thymus serpyllum herb and Taraxacum officinale leaf extracts. These results allowed us to conclude their potential application in medicine to support the treatment of challenging wound conditions.
Keywords: Asteraceae; Galium aparine; Lamiaceae; Rubiaceae; Taraxacum officinale; Thymus serpyllum